Analysis of Entrepreneurship Education Achievements Using the Project Based Learning (PJBL) Model in MBKM Curriculum - Khotimah, Sofiatul; Amrullah, Andi; Octoria, Dini; Aysi, Siti Aenandari Hadatul (Universitas Muhammadiyah Surakarta, 2022)
The purpose of this research is to analyze the achievement of entrepreneurship learning using the project-based learning (PjBL) model in the MBKM curriculum at Jenderal Soedirman University. The achievement indicator of MBKM in entrepreneurship activity at Jenderal Soedirman University is the students can practice entrepreneurship by using a comprehensive understanding of entrepreneurial concepts. The research method used is quasi-experimental (quasi-experimental) with data analysis used paired sample t-test to see whether there is an influence on learning achievement with the valuation of cognitive (knowledge), affective (attitude), and psychomotor (capability). Data was collected using pre-test and post-test on students. The results of paired sample t-test on learning achievement in cognitive, affective, and psychomotor are 0.001 < 0.05, 0.000 < 0.05, dan 0.000 < 0.05, respectively. Based on this research it can be concluded that the implementation of the PjBL model affects the understanding level of students both cognitively, affectively, and psychomotor.